Risk factor analysis of chronic kidney diseases using based on case control study - CHEN Zhi-hong; LU Chun-jian; YUAN Chang-jian; CAI Yu-chun; YI Wu-yong (Linchuang shenzangbing zazhi)
Objective To study the risk factors of chronic kidney disease(chronic kidney disease,CKD) based on case-control study. Methods In the period from January 2017 to June 2018, 243 patients diagnosed with CKD were selected as the CKD group, and 292 patients with non-kidney disease, who were examined in Shenzhen TCM Hospital, were taken in a way of random sampling as the control group. Through the retrospective analysis of the clinical data and the questionnaire(the main content is the life state of the last year), the relevant risk factors that affect onset of CKD were analyzed, such as basic conditions, infection in the last year, hyperlipidemia, hypertension, diabetes, hyperuricemia,hyperuricemia, cardiovascular diseases. eating habits, sports habits,etc. Results There were significant differences in sex, age, hyperlipidemia, diabetes, hypertension, cardiovascular disease, infection,salty diet, drinking water type and daily dairy intake between the two groups(P<0.05). Multivariate regression analysis showed that the frequency of colds(frequent), hypertension, hyperuricemia and drinking water(bottled water) were the independent risk factors for CKD. Their ORs(95%CI) were 2.511(1.109), 3.825(2.167), 4.352(2.523 ～ 7.509), 1.676(1.026 ～ 2.737), respectively. Conclusions It is very important to early find the risk factors leading to onset of, and conduct comprehensive prevention and treatment actively, which are crucial for reducing incidence of CKD and standardizing health management of CKD.